Revitalizing the Image of Islamic Boarding Schools in Addressing the Crisis of Societal Stigma Through Digital Platforms - SANAFIRI, Ahmad Nadif (PT Batara Swastika Harati, 2024)
This study aims to explore how digital strategies employed by Islamic boarding schools (pesantren) can be used to improve their image and address societal stigma. The primary focus is on understanding the role of digital content, user engagement, and feedback in shaping public perceptions of pesantren. The research adopts a qualitative method with a case study approach to gain an in-depth understanding of the topic. The research subjects include the administrators of Nurul Jadid Islamic Boarding School, who are involved in the creation and management of digital content, as well as the audience actively interacting with pesantren content across various digital platforms such as social media, websites, and videos. Data collection techniques involve in-depth interviews with pesantren administrators and the audience to explore their experiences, perceptions, and feedback. Additionally, content analysis of user feedback on digital platforms is employed to enrich the information collected. Data analysis techniques include transcription of interviews, coding of qualitative data, and thematic analysis to identify key themes and patterns. Data from user feedback is analyzed to understand engagement and responses to pesantren content. The findings indicate that positive and informative digital content, such as stories of students and alums, significantly improves public perception of pesantren. Digital platforms enhance the image of pesantren, with audience engagement and responses to user feedback being key factors. This research highlights the importance of responsive digital strategies in building a better image in the eyes of the public.